Chemical principles - Zumdahl, Steven S.; DeCoste, Donald J. (Brooks/Cole Cengage Learning, 2013)
Designed for students with solid mathematical preparation, this best-seller offers a unique organization that emphasizes models, everyday applications of chemistry, and a thoughtful, step-by-step problem-solving approach.